1995
DOI: 10.1088/0268-1242/10/2/007
|View full text |Cite
|
Sign up to set email alerts
|

A comparative electron paramagnetic resonance study of vanadium in n-type, semi-insulating and p-type CdTe

Abstract: A quantitative electron paramagnetic resonance (EPR) study of vanadium-related defects in semi-insulating and co-doped p-type and n-type bulk CdTe:V shows the Vcd donor to be the dominant electrically and optically active 4 x l O I 5 c m 3 for the defect, determined by quantitative EPR spectroscopy, is in agreement with the value obtained from photorefractive measurements on the same crystals. A comparison of the total V content with the Vcd donor concentration indicates the existence of additional V-related d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…1), which gives ͓V 3ϩ ͔ ϭ 6 ϫ 10 15 cm Ϫ3 for B23 and ͓ V 3ϩ ͔ ϭ 35 ϫ 10 15 cm Ϫ3 for B28. 4 Concerning the calibration of the MCD P 2 band related to V 2ϩ , we have , we thus observe a decrease in the V 3ϩ intensity; at 1.06 m (c), an increase, always compared with the thermal equilibrium value. Typical excitation intensities are 10 W cm Ϫ2 , and the spectrum intensity achieves an equilibrium value after typically a few minutes.…”
Section: Magneto-optical and Optical Absorption Studiesmentioning
confidence: 59%
See 1 more Smart Citation
“…1), which gives ͓V 3ϩ ͔ ϭ 6 ϫ 10 15 cm Ϫ3 for B23 and ͓ V 3ϩ ͔ ϭ 35 ϫ 10 15 cm Ϫ3 for B28. 4 Concerning the calibration of the MCD P 2 band related to V 2ϩ , we have , we thus observe a decrease in the V 3ϩ intensity; at 1.06 m (c), an increase, always compared with the thermal equilibrium value. Typical excitation intensities are 10 W cm Ϫ2 , and the spectrum intensity achieves an equilibrium value after typically a few minutes.…”
Section: Magneto-optical and Optical Absorption Studiesmentioning
confidence: 59%
“…Section 2 deals with an EPR study of the different crystals. The EPR results have allowed us to determine the Fermi-level position and the corresponding V configurations in the codoped samples, to measure quantitatively the V 3ϩ defect concentrations [2][3][4][5][6][7] and to test the directly photoinduced variations of the V 3ϩ charge state in the semi-insulating (B23) sample. Section 3 deals with a magneto-optical study of the different crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Bylsma et al [2] for the first time reported the observation of the photorefractive effect in vanadium-doped CdTe crystals at 1.06 µm. Other photorefractive studies [3,4] as well as investigations of EPR, photo-EPR and optical spectra [5][6][7][8][9] of CdTe:V crystals were carried out. The modern state of investigations of photorefractive semiconductor materials shows that it is important to carry out detailed studies of their different physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…V 3+ ions, in comparison with the concentration of other electron traps, namely the neutral cadmium vacancies and the neutral acceptor complexes. The concentration of V 3+ ions in CdTe:V crystals usually is about 10 16 cm −3 [16]. Therefore it can happen that the concentration of the neutral V o Cd and (V − Cd + D + ) 0 acceptors in the CdTe:V crystals investigated is less than 10 16 cm −3 .…”
Section: Time-resolved Photoelectric Measurementsmentioning
confidence: 94%
“…Among the semiconductors crystals, taking into account their physical parameters, CdTe doped with 3d elements are very promising for applications in the areas of optical communication, optical storage, image recognition, optical computing and optoelectronics [1]. Previous studies of such materials have mainly concentrated on the analysis of the photorefractive properties [2][3][4] as well as of electron paramagnetic resonance (EPR), photo-EPR and optical spectra [5][6][7][8]. It should be noted that 3 Author to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%